ABOUT HAUSDORF’S MEASURE OF GREAT NUMBER OF VALIRON DEFECTIVE VECTORS OF ENTIRE CURVE - Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
More precisely metrical description of Valiron defect vectors of entire curve of continuity order is given than known earlier.